DIVERGENT THINKING IN A STANDARDIZED TEST - Ismail, Nyak Mutia; Moriyanti, Moriyanti; Yusnida, Dara (Indonesian Journal of Learning and Instruction, 2019)
In dealing with standardized tests, including TOEFL test, there is a common propensity for test-takers to adopt convergent thinking which is a cognitive process in retrieving a pre-existing answers using concepts, knowledge, and understandings. On the contrary, the use of divergent thinking in standardized tests is scarce because the test-takers do not create new knowledge or ideas during the test. This study sought whether higher divergent thinking ability could affect TOEFL score. A case study was employed to gather the data from 143 respondents (divided into two groups: each 73 and 70 students) whom of which were 3rd year Economics students at Syiah Kuala University. Guilford’s Alternative Uses Test was used as the instrument where the students should name the functions of a stone in 5 minutes. The total of 538 responses from group A and 366 from group B were obtained from this test. The data were analyzed using the descriptive statistics in terms of its originality. The results showed that the group whose ability in divergent thinking is higher could achieve average score reaching 523, while those with less ability in employing divergent thinking could only attained 477 in average. The findings imply that in teaching TOEFL preparation or other standardized tests, divergent teaching technique needs to be employed as the instructors should expands students’ thinking by not only limiting it to Question-Answer technique.